Crime Distribution and Victim Behavior during a Crime Wave - Rafael Di Tella; Sebastian Galiani; Ernesto Schargrodsky (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2006)
The study of how crime affects different income groups faces several difficulties. The first is that crime-avoiding activities vary across income groups. Thus, a lower victimization rate in one group may not reflect a lower burden of crime, but rather a higher investment in avoiding crime. A second difficulty is that, typically, only a small fraction of the population is victimized so that empirical tests often lack the statistical power to detect differences across groups. We take advantage of a dramatic increase in crime rates in Argentina during the late 1990s to document several interesting patterns. First, the increase in victimization experienced by the poor is larger than the increase endured by the rich. The difference appears large: low-income people have experienced increases in victimization rates that are almost 50 percent higher than those suffered by high-income people. Second, for home robberies, where the rich can protect themselves (by hiring private security, for example), we find significantly larger increases in victimization rates amongst the poor. In contrast, for robberies on the street, where the rich can only mimic the poor, we find similar increases in victimization for both income groups. Third, we document direct evidence on pecuniary and non-pecuniary protection activities by both the rich and poor, ranging from the avoidance of dark places to the hiring of private security. Fourth, we show the correlations between changes in protection and mimicking and changes in crime victimization. Fifth, we offer one possible way of using these estimates to explain the incidence of crime across income groups.
Keywords: K42; 330; Victimization; income distribution; private security; victim adaptation.